2008
DOI: 10.1007/s10661-008-0427-y
|View full text |Cite
|
Sign up to set email alerts
|

Soil solution and sugar maple response to NH4NO3 additions in a base-poor northern hardwood forest of Québec, Canada

Abstract: Nitrogen additions (NH4NO3) at rates of three- and ten-fold ambient atmospheric deposition (8.5 kg ha(-1) year(-1)) were realised in an acid- and base-poor northern hardwood forest of Québec, Canada. Soil solution chemistry, foliar chemistry, crown dieback and basal area growth of sugar maple (Acer saccharum Marsh.) were measured. Except for a transitory increase of NO3 and NH4 concentrations, there was no persistent increase in their level in soil solution 3 years after N treatments, with the exception of one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 78 publications
3
9
0
Order By: Relevance
“…In line with our results, Moore and Houle [46] found a significant increase in soil nitrate-N and ammonium-N after N fertilization in a northern hardwood forest in Québec. N addition experiments in coniferous and boreal forests in Sweden showed that soil nitrate-N and ammonium-N contents increased following N addition treatment [47], [48].…”
Section: Discussionsupporting
confidence: 92%
“…In line with our results, Moore and Houle [46] found a significant increase in soil nitrate-N and ammonium-N after N fertilization in a northern hardwood forest in Québec. N addition experiments in coniferous and boreal forests in Sweden showed that soil nitrate-N and ammonium-N contents increased following N addition treatment [47], [48].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, decreasing exchangeable cation concentrations associated with soil acidification caused by N and S deposition can exacerbate nutrient imbalance such as deficiency of Mg and K for tree growth (Erisman and De Vries, 2000). Based on our results, the studied ecosystem did not show any signs of N saturation after 4 yr of N addition, which was consistent with previous research in other study sites with similar application rates (Moore and Houle, 2009;Sogn and Abrahamsen, 1998). Meanwhile, significant reduction of exchangeable cation concentrations in the mineral soil caused by N and/or S additions (Table 1) may imply potential long-term risk of nutrient imbalance in the studied boreal forest.…”
Section: Plant Growth Responses To Simulated N and S Depositionssupporting
confidence: 91%
“…It is consistent with results in the accelerated N addition study in eastern Canada reporting no N saturation with deposition rates ranging from 9 to 85 kg N ha À1 yr À1 (Houle, 2006;Moore and Houle, 2009). On a long-term basis, however, 10 kg N ha À1 of deposition has been regarded as a threshold likely to lead to significant N leaching based on data from 126 forest sites in Europe and North America (Dise and Wright, 1995;Stoddard et al, 2001).…”
Section: Soil N and Nitrate Leaching Responses To Simulated N And S Dsupporting
confidence: 90%
See 1 more Smart Citation
“…Because dry S deposition is relatively low in the study area, the fact of not considering them along with annual variation of precipitation SO 4 in our analysis, should not have important impacts on our results. Deposition of inorganic N (or precipitation concentration) was not retained as an explanatory variable because N catchment budgets and experimental addition of N at forested sites located within or close to the study area [ Duchesne and Houle , 2006; Houle et al , 1997; Houle and Moore , 2008; Moore and Houle , 2009] indicated that atmospheric N is extensively retained within catchments, thereby, not affecting the acid‐base status of our lakes. The high N retention in catchments can also be deduced from low NO 3 concentration in the lakes network (see section 3.2).…”
Section: Methodsmentioning
confidence: 99%